Safety of Beta‐lactoglobulin as a Novel food pursuant to Regulation (EU) 2015/2283. (8th April 2022) - ,; Turck, Dominique; Bohn, Torsten; Castenmiller, Jacqueline; De Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Pelaez, Carmen; Pentieva, Kristina; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on beta‐lactoglobulin (BLG) as a novel food (NF) pursuant to Regulation (EU) 2015/2283. The NF (≥ 90% w/w dry matter protein) consists of BLG as primary component (≥ 90% of total protein), which is equivalent to BLG present in bovine milk and whey protein isolate (WPI). The NF is produced from bovine whey by crystallisation under acidic or neutral conditions. The NF is proposed to be used as a food ingredient in isotonic and sport drinks, whey powder and milk‐based drinks and similar products, and in food for special medical purposes as defined in Regulation (EU) No 609/2013. The target population is the general population. The highest daily intake of the NF was estimated for children of 3 to < 10 years of age as 667 mg/kg body weight (bw) per day. The NF presents proximate composition and content of essential amino acids similar to those in WPI. The Panel notes that the highest mean and highest 95th percentile daily protein intakes from the NF are below the protein population reference intakes for all population groups. Although a tolerable upper intake level has not been derived for protein, the protein intake from the NF may nevertheless further contribute to an already high dietary protein intake in Europe. The exposure to the reported minerals does not raise concerns. The Panel considers that the consumption of the NF is not nutritionally disadvantageous. No genotoxic concerns were identified from the standard in vitro test battery. No adverse effects were observed in the subchronic toxicity study, up to the highest dose tested, i.e. 1, 000 mg NF/kg bw per day. The Panel concludes that the NF is safe under the proposed conditions of use.